Service-Learning and the Development of Nursing Students’ Cognitive Skills and Professional Values - จิโรจน์กุล, ประกาย; สุขเจริญ, พิไลพร; นิปัทธหัตถพงศ์, สมจิต; บาลจ่าย, ญาดารัตน์ (Nursing Journal of The Ministry of Public Health, 2018)
Abstract This article presents the definition, and type of service-learning. It also discusses the application of service learning on the development of nursing students’ cognitive skills and professional values. Examples from research studies and the reflection of students who participated in our previous service-learning activities are provided. The details of service-learning process, which we have synthesized from our experiences at Suan Dusit University are also illustrated for the benefit of readers who are interested in applying service-learning as a student competency development tool.